Risk Management of West Semarang Water Supply PPP Project: Public Sector Perspective - Jati Utomo Dwi Hatmoko; Riza Susanti (IPTEK Journal of Proceedings Series, 2017)
While the need for water supply infrastructure development keeps increasing, many local governments of Indonesia are facing problems related to limited funding. This condition opens up an opportunity for private sector to invest in water supply infrastructure projects through Public Private Partnership (PPP) scheme. As this scheme is relatively new for many local governments in Indonesia, its complexity and typically long duration of the concession period may raise concerns of potential risks throughout the project life cycle. It is, therefore, very important for public sector as owner of the project to understand and to be able to manage risks properly throughout the concession period. The aim of this research is to evaluate risk management of West Semarang Water Supply PPP Project as perceived by public sector. The objectives are to identify, to analyze, and to allocate risks to the right parties. Qualitative and quantitative approaches have been used for the research method. Data were collected through focus group discussion involving 16 relevant officials of local government of Semarang, including its Regional Water Supply Company (PDAM). This research has identified a total of 66 risks as perceived by the public sector, which are then classified into 11 categories, e.g. political, operation, revenue, etc. The proportions of the level of risks are relatively balanced, as follows; low (37.88%), moderate (28.79%) and high (33.33%). In terms of risk allocation, 46.97% of risks are allocated to the public sector, while 37.88% and 15.15% of the risks are allocated to the private sector and shared by both parties, respectively. The results of this research are valuable for the local government of Semarang and can be used as a guidance in managing risks of the PPP project throughout the concession period.